Hacking Science: The ALivE Group's Material Design Methods for Interdisciplinary Environments. (September 2015) - Bechthold, Martin; Sayegh, Allen; Menges, Achim
<x xml:space="preserve">Abstract</x> Advances in the understanding and processing of materials have historically been one of the foremost drivers of architectural innovation. Today, groundbreaking material developments mainly occur on the nano‐scale, and thus lie outside most designers' working knowledge and expertise. Martin Bechthold, Professor of Architectural Technology at the Harvard Graduate School of Design (GSD), and Allen Sayegh, Associate Professor in Practice of Architectural Technology at the GSD, introduce the work of the Adaptive Living Environments (ALivE) group at Harvard University, which seeks to reconcile fundamental material science with architectural design through new modes of interdisciplinary collaboration drawing from contemporary cultures of computation and hacking.